The Wall - Taylor-Johnson, Aaron; Cena, John; Nakli, Laith ([United States] : Lionsgate, 2017)
Follows two soldiers pinned down by an Iraqi sniper, with nothing but a crumbling wall between them. Their fight becomes as much a battle of will and wits as it is of lethally accurate marksmanship.
Director, Doug Liman.
Aaron Taylor-Johnson, John Cena, Laith Nakli.
MPAA rating: R for language throughout and some war violence.
DVD, 16x9 Widescreen 2.39:1, Dolby Digital 5.1.
English audio; Spanish subtitles.
English subtitles for the deaf and hard of hearing.
Keywords: Drama; Action / Adventure; War; Action; Thriller films